TRADE FAIRS IN TURKESTAN AND CULTURAL INTERACTION OF PEOPLES - Yekaterina Alexandrovna Smesova (Journals Park Publishing, 2024)
The article analyzes trade fairs in Turkestan and the cultural mutual influence of peoples with the help of historical documents and archival sources. Besides, in the research showed that in the second half of the 19th century, in Russia and a number of European countries, interest in the history and culture of the peoples of Central Asia increased, especially in handwritten publications on ethnography and history, and in antique items made by skilled Central Asian craftsmen.
Keywords: Turkestan Governor-General, Syr-Darya, European countries, Turkestan region, Russia, centralized collection, handwritten publications.